Towards achieving environmental sustainability: environmental quality versus economic growth in a developing economy on ecological footprint via dynamic simulations of ARDL - Solarin, Sakiru Adebola; Nathaniel, Solomon P.; Bekun, Festus Victor; Okunola, Akinbode Michael; Alhassan, Abdulkareem (Springer Heidelberg, 2021)
Studies have shown that factors like trade, urbanization, and economic growth may increase the ecological footprint (EFP) since ecological distortions are mainly human-induced. Therefore, this study explores the effect of economic growth and urbanization on the EFP, accounting for foreign direct investment and trade in Nigeria, using data from 1977 to 2016. This study used the EFP variable as against the CO2 emissions used in the previous studies since the former is a more comprehensive and extensive measure of environmental quality. We apply the novel dynamic autoregressive distributed lag (ARDL) simulations for model estimation, the Bayer and Hanck J Time Ser Anal 34: 83-95, (2013) combined cointegration, and the ARDL bounds test for cointegration. Although the results affirmed the presence of long-run relationship among the variables, economic growth deteriorates the environment in the short run, while urbanization exacts no harmful impact. In the long run, FDI and trade deteriorate the environment while economic growth adds to environmental quality. It is recommended that policymakers strengthen the existing environmental regulations to curtail harmful trade and provide rural infrastructures to abate urban anomaly.
Keywords: Economic growth; Urbanization; Trade; FDI; Ecological footprint; Nigeria